New insights into cycling of 231Pa and 230Th in the Atlantic Ocean - Rempfer, Johannes; Stocker, Thomas F.; Joos, Fortunat; Lippold, Jörg; Jaccard, Samuel L. (Earth and planetary science letters, 2017)
We use the Bern3D model of intermediate complexity to examine the marine cycle of isotopes 231Pa and 230Th and the relationship between the particle-bound ratio Pap/Thp and changes in the formation of the North Atlantic Deep Water (NADW). Model parameters describing reversible scavenging of isotopes by organic particles, opal, calcite and resuspended sediments were systematically varied and alternative sink parametrisations explored. It proves difficult to simultaneously achieve a good agreement with observations of dissolved and particle-associated concentrations of 231Pa and 230Th (Pad, Thd, Pap, Thp) as well as the particle-bound ratio Pap/Thp within the classical concept of reversible scavenging alone. Agreement between simulated and observed Pad, Thd and estimates of mean ocean residence times is improved by taking into account simplified representations of additional sinks at the sea floor (bottom scavenging) and at continental boundaries (boundary scavenging). We also find improved agreement between model and data by increasing lateral advection, in particular for Pad. These results point to the importance of sink processes that act in addition to reversible scavenging to shape the steady state distribution of 231Pa and, to a lesser degree, of 230Th. In transient experiments in which the strength of the Atlantic meridional overturning circulation (AMOC) is periodically turned on and off, we find a strong statistical relationship between variations in AMOC strength and Pap/Thp at great depths in the Northwest Atlantic region. These conclusions are robust across the range of sink parametrisations, that are consistent with estimates in the mean ocean residence time of 231Pa and 230Th. Our results indicate that the relationship between Pap/Thp and AMOC-strength may not be fundamentally affected by uncertainties in sink processes, at least on the large spatial and temporal scale considered here, and support the idea that changes in Pap/Thp in sediments of the Northwest Atlantic are indicative of changes in AMOC strength. Taking into account our simplified approach, our results indicate that the relationship between Pap/Thp and AMOC-strength in the deep Northwest Atlantic is not affected by boundary scavenging or bottom scavenging. Our results thus support the idea that changes in Pap/Thp in sediments of the Northwest Atlantic are indicative of changes in AMOC strength.
Available online: 10 April 2017
Gesehen am 21.07.2021
Die Zahlen im Titel sind hochgestellt